ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI VARIETAS UNGGUL LOKAL DAN VARIETAS HIBRIDA PADA SAWAH TADAH HUJAN DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Jamalludin Jamalludin (DINAMIKA PERTANIAN, 2016)
The purpose of this study was to determine the factors that influence the production of rainfed rice production of local varieties and hybrids in the District of Seberang Bangkinang. This study used survey method. The sampling technique rainfed rice farmers carried out using methods Malti Stake Sampling and the number of farmers as many as 90 people. Simultaneous use of production factors of land, seed, Urea, SP36 fertilizer, NPK, organic fertilizer, pesticides and labor of the use of different varieties provide a significant influence. Based on the coefficient determinant for both varieties known that these variables can influence the production of varieties Super Bernas amounted to 91.0% and the Variety Children Daro by 69.9%. In the varieties of Children Daro independent variables were significant and very real is the Pesticides (X4), while the varieties Super pithy independent variable significant effect is Fertilizer SP 36 (X23), Organic Fertilizer (X34), pesticides (X4) and labor (X5).